Frequency of Hypothyroidism in HCV Positive Patients at Chandka Medical College Teaching Hospital Larkana (Medical Forum Monthly, 2024)
Objective: To determine the frequency of hypothyroidism in hepatitis C patients presenting to tertiary care Hospital. Study Design: Case Series study Place and Duration of Study: This study was conducted at the Medical Unit-I Chandka Medical, Larkana from January 2019 to July 2019. Materials and Methods: The study was conducted on patients following inclusion and exclusion criteria and ethical approval and informed consent. The blood samples for TSH, T3 and T4 levels were sent to the laboratory of Larkana Institute of Nuclear Medicine and Radiotherapy (LINAR). Results: Our results have shown that some 4 (4.9%) patients were diagnosed as hypothyroid patients, being more common in females and younger age. Conclusion: We propose a massive epidemiological study not only to gather the relevant data but also focusing on some of the factors and reasons for co existence of hypothyroidism and HCV. HCV patients should also provided information regarding side effects of its treatment, among which is most commonest is hypothyroidism.